Multicultural Values Representation in the English Textbook â€œEnglish in Mindâ€ for Junior High School - Habibah, Rifdatul; Hidayat, Didin Nuruddin; Husna, Nida; Alek, Alek (Institut Agama Islam Negeri Palopo, 2024)
This research aims to look into the multicultural values represented in the Merdeka Curriculum textbook for Junior High School,